Staphylococcus saprophyticus native valve endocarditis in a diabetic patient with neurogenic bladder: A case report. Issue 9 (September 2015) - Magarifuchi, Hiroki; Kusaba, Koji; Yamakuchi, Hiroki; Hamada, Yohei; Urakami, Toshiharu; Aoki, Yosuke
Abstract A 61-year-old man was admitted to our hospital with 2-day history of malaise and dyspnea. He had mitral prolapse and type II diabetes mellitus with neurogenic bladder, which was cared for by catheterization on his own. On arrival the patient was in septic condition with hypoxemia, and physical examination revealed systolic murmur at the apex. Transthoracic echocardiography revealed vegetation of the mitral and the aortic valve. The presence of continuous bacteremia was confirmed by multiple sets of blood culture, whereby gram-positive cocci was retrieved and identified as Staphylococcus saprophyticus (S. saprophyticus) both phenotypically and genetically. Because two major criteria of the Modified Duke Criteria were met, the patient was diagnosed with native valve endocarditis due to S. saprophyticus. The urine culture was also positive for gram-positive cocci, phenotypically identified as Staphylococcus warneri, which was subsequently identified as S. saprophyticus with the use of 16S rRNA gene sequence analysis and MALDI-TOF MS (matrix-assisted laser desorption ionization time of flight mass spectrometry), indicating strongly that the intermittent catheterization-associated urinary tract infection resulted in bacteremia that eventually lead to infective endocarditis. This patient was treated with vancomycin and clindamycin. Because of multiple cerebral infarctions, the patient underwent mitral and aortic valve replacement on hospital day 5. Blood culture turned negative at 6th hospital day. Antibiotic therapy was continued for six weeks after surgery. The patient's clinical course was uneventful thereafter, and was discharged home. This is the first case report of native valve endocarditis caused by S. saprophyticus of confirmed urinary origin.